PUSAT PENANGKARAN DAN KERAJINAN KULIT BUAYA - Yosi Valentina Simorangkir; Muchlis Alahudin; Jeni Paresa (Musamus Journal of Architecture, 2019)
One of the works of the town of Merauke that is quite proud of is crocodile leather craft. Currently in the city of Merauke there is no Center for Capturing and Craft of Crocodile Skin which houses crocodile leather craftsmen where the results of processed crocodile skin are very diverse, so as to boost local revenue. By seeing the natural condition of Merauke which has a tropical climate, it is necessary to have a design approach that takes into account environmental conditions. The method used in this research is qualitative method. This research data in the form of primary data and secondary data obtained by conducting direct interviews and observations and reinforced with photo documentation. The results of this study are a design based on the design and design concept of Education and Learning Center of Crocodile Breeding which is educational (learning) so that visitors can know the process of hatching, tanning, to being processed crocodile skin products, which pay attention to architectural rules that pay attention to lighting lighting and natural disposition and pay attention to environmental conditions in accordance with the concept of Modern Tropical design.